The Norm of Rate Fixing of Islamic Banks Based on Conventional Bank Rates: Evidence from Indonesia - Fakhrina, Agus; Islahuddin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Interest rate fixing is a monetary tool used to control the money supply and hence inflation by the central bank. However, it cannot be applied to Islamic banks due to the prohibition of interest in Islam. This paper examines whether the central bank may implement rate fixing for Islamic banks, given that interest is forbidden, and the fixing of prices by the government is also generally prohibited, according to Hadith and the consensus of Islamic jurists. A documentation study was conducted to comprehend the viewpoints of classical and contemporary Islamic jurists and the National Shariah Board−Indonesian Ulama Council's fatwa. The analysis used Islamic law methodology (uşūl fiqh), which included combining the opinions of classical and contemporary Islamic jurists through the al-jam’u and the legal maxim approach,